Voter preferences, voter manipulation, voter analytics: policy options for less surveillance and more autonomy - Jacquelyn Burkell; Priscilla M. Regan (Internet Policy Review, 2019)
Researchers in psychology have long known that preferences are constructed in the decision-making process, influenced by choice environments that trigger unconscious biases and heuristics. As a result, choices, including those of voters, can be manipulated by political information. Personalised political messages, designed to influence based on detailed personal profiles, can undermine voter autonomy. We suggest that these practices should therefore be regulated, and discuss policy options and approaches, specifically the appropriate balance between freedom of political speech and privacy rights and interests, the implications of voter analytics for the electoral process, and how and by whom sophisticated voter analytics practices should be regulated.
Keywords: 300; Political autonomy; Micro-targeting; Privacy; Surveillance; Voting behaviour